2022
DOI: 10.1007/s13201-021-01566-3
|View full text |Cite
|
Sign up to set email alerts
|

A review on the capability of zinc oxide and iron oxides nanomaterials, as a water decontaminating agent: adsorption and photocatalysis

Abstract: Water decontamination became a priority-based focused area for environmental scientists and researchers these days. Several contaminants like pesticides (chlorpyrifos, endosulfan, aldrin, lindane, malathion) and heavy metals (As, Pb, Cd, Hg, Cu) are broadly reported in drinking water worldwide. Pesticides and heavy metals build up in drinking water is a danger to all consumers. These pollutants cause a number of deadly diseases like bone deformity, nerve disorder, liver damage and cancer. So, their elimination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 109 publications
0
9
0
Order By: Relevance
“…This fact, plus their lowest cost, makes it possible to consider iron compounds for use in natural waters. Studies of Jack et al (2015), Li et al (2007) and Bharti et al (2022) indicated iron compounds can be effective for natural water purification from organic substances. Nevertheless, this issue requires further research.…”
Section: Photodegradation Of Xenobiotics In Surface Watermentioning
confidence: 99%
“…This fact, plus their lowest cost, makes it possible to consider iron compounds for use in natural waters. Studies of Jack et al (2015), Li et al (2007) and Bharti et al (2022) indicated iron compounds can be effective for natural water purification from organic substances. Nevertheless, this issue requires further research.…”
Section: Photodegradation Of Xenobiotics In Surface Watermentioning
confidence: 99%
“…ZnO NPs and their nanocomposites were explored to adsorb various industrial dyes in addition to other water pollutants, and previous studies showed that zinc oxide is an effective adsorbent for removing many pollutants (Bharti et al 2022;Zafar et al 2019). ZnO is biocompatible and facile in synthesis, while environmental situations do not alter its structural properties (Mohd et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, various studies on the adsorption of heavy metals and radionuclides onto ZnONPs have been conducted (Kumar et al 2013;Kaynar et al 2014;Azizi et al 2017;Lagashetty et al 2020;Gu et al 2020;Alqahtany and Khalil 2021;Davarnejad and Nikandam 2022). Due to the importance of ZnONPs in water treatment, a review of their capability as a water decontaminating agent via adsorption and photocatalysis was written (Bharti et al 2022). Another review recorded the synthetic parameters influencing the characteristics of ZnONPs and their use in wastewater treatment (Shaba et al 2021).…”
Section: Introductionmentioning
confidence: 99%